Pharmacophore Mapping, In Silico Screening and Molecular Docking to Identify Selective Trypanosoma brucei Pteridine Reductase Inhibitors. Issue 2 (2nd February 2014) - Dube, Divya; Sharma, Sujata; Singh, Tej P.; Kaur, Punit
Abstract Trypanosoma brucei Pteridine reductase (TbPTR1) is of vital importance and is an established drug target for dreaded Human African trypanosomiasis (HAT). Pharmacophore perception strategy has been employed to identify key chemical features responsible for the biological activity for TbPTR1. The findings suggest that three different pharmacophore features can be associated with T. brucei anti‐PTR1 activity namely: H‐bond donors (D), Hydrophobic aromatic (H) and Ring aromatic (R). The resulting hypothesis is able to predict the activity of other existing TbPTR1 inhibitors with a correlation coefficient (r) of 0.89. An in silico database screening, based on the best hypothesis, has been used to identify some potential nanomolar range TbPTR1 inhibitors. These compounds were then checked by molecular docking and subjected to ADMET analysis. Further, a detailed comparison of the pharmacophore behavior and differential analysis of binding pockets of T. brucei and L. major was made which revealed subtle differences in terms of their shape and charge properties. This investigation can form the basis for tweaking the specificity of compounds for generating new improved species specific inhibitor molecules for Pteridine reductase in these different parasitic protozoans.